Spiritualitas Modern Melalui Wisata Religi - Sari Narulita (Proceedings of Annual Conference for Muslim Scholars, 2018)
This research tries to reveal the phenomenon of increased spirituality among society in DKI Jakarta, in response to the negative impacts of modernism. The revival of urban spirituality as an icon of modern society is marked by the passion of the people who follow various activities of spirituality, such as doing routine reciting holy Quran in various mosques, religious halaqah, religious teaching, and also prefer to do it in quiet areas and pursue activities that are considered capable of reassuring soul, which in this study focused on the pilgrimage of the tomb of Habib Husein Alydrus, Luar Batang. The result of the research shows the form of the meaning of modern spirituality, namely 1) Meaning of Life, which is shown by understanding the good relationship between self and the Almighty, 2) Peace of heart, body, and mind obtained by contemplation, and reading of verses holy. Further peace spreads to the mind and manifests itself in attitude or behavior. This calm and peaceful attitude will have implications for the relationship or connection with others and the environment; and 3) The strengthening of human values in the form of; empathy, courage, justice, and love.